Is There a Link between Welfare Regime and Attitudes toward Climate Policy Instruments? - Sivonen Jukka; Kukkonen Iida (SAGE PUBLICATIONS INC, 2025)
We explore the relationship between welfare regime and climate policy attitudes. The synergy hypothesis suggests that social and environmental policies can reinforce each other. Thus, more universal and generous welfare state model (i.e., welfare regime) is said to provide especially fertile ground for advancing climate policies. Using multilevel modeling and European Social Survey Round 8 data (including 23 countries in Europe and Israel), we test whether this hypothesis applies at the attitudinal level. Moreover, we hypothesize that country-level political trust predicts support for climate policy instruments. The study focuses on three instruments: fossil fuel taxation, subsidizing renewable energy, and banning energy-inefficient household appliances. The results indicate that welfare regime is significantly related to attitudes toward taxation, but less significantly toward subsidizing and banning. Political trust predicted support for all instruments, but the effect was particularly strong for taxation. The results highlight the importance of welfare structures in climate politics.